Natural Disasters, Human Development and Poverty at the Municipal Level in Mexico - Rodriguez-Oreggia, Eduardo; de la Fuente, Alejandro; de la Torre, Rodolfo; Moreno Moreno, Hector A. (Taylor and Francis, 2013)
This article analyses the effects of natural disasters on human development and poverty levels at the municipal level in Mexico. Using several sources, we build a panel of data in order to uncover if different natural shocks can affect social indicators. After controlling for geographic and natural characteristics which can make municipalities more hazard prone, as well as for other institutional, socio-economic and demographic pre-shock characteristics, in addition to using fixed effects, we find that general shocks, especially from floods and droughts, lead to significant drops in both types of indicator.